Baseline resistance and cross-resistance among fluoroquinolones in multidrug-resistant Mycobacterium tuberculosis isolates at a national reference laboratory in India. (March 2018) - Mamatha, H.G.; Shanthi, V.
Highlights: Fluoroquinolones (FQs) are second-line drugs used in the treatment of MDR-TB. Importance of performing baseline drug susceptibility testing for FQs in MDR-TB patients. Theory of complete cross-resistance among FQs needs to be checked. Need for a policy guideline to end the irrational use of FQ drugs. Abstract: Objectives: Pre-existing fluoroquinolone (FQ) resistance in multidrug-resistant tuberculosis (MDR TB) patients is a major threat in treating MDR-TB. This study was conducted to assess the percentage of FQ resistance among MDR-TB patients and to determine whether there is complete cross-resistance between FQs [ofloxacin (OFX), levofloxacin (LVX) and moxifloxacin (MXF)] used as second-line drugs in MDR-TB treatment. Methods: Among 879 MDR-TB suspects tested, 68 were confirmed to be MDR-TB and rifampicin (RIF) monoresistant. Suspects were further analysed for FQ resistance by drug susceptibility testing (DST) using Mycobacterium Growth Indicator Tube (MGIT). Minimum inhibitory concentrations (MIC) were determined for OFX, LVX and MXF. Results: Of 879 MDR-TB suspects, RIF resistance was observed in 70 patients (8.0%), among which pre-existing FQ resistance was detected in 32%. Moreover, 88% of isolates exhibited a similar DST pattern for all three FQs tested. Cross-resistance among FQs was not complete in eight isolates; the MIC of MXF was found to be much lower than the MICs of OFX and LVX. Conclusions: A huge proportion of MDR-TB strains (32%) exhibiting OFX resistance prior to treatment with second-line anti-TB drugs raises major concern. Detection of baseline drug resistance in TB patients helps in reducing the transmission of drug-resistant TB. The OFX MIC was higher than its critical concentration, indicating the prevalence of baseline resistance to FQs owing to irrational use of these drugs.